TEACHING WITH TECHNOLOGY. - Akhmadqulova Dilbar Farkhadjon qizi; Dekhqonboyeva Go’zal Alisher qizi; G’aforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In this article about,utilizing technology in teaching.It shows the significant towards of technology, compares strong and weak points of technology,role of teaching and learning in developing world and education system.